Early-Stage Ruptured Hepatocellular Carcinoma With Different Tumor Diameters: Small Tumors Have a Better Prognosis - Xia, Feng; Huang, Zhiyuan; Zhang, Qiao; Ndhlovu, Elijah; Zhang, Mingyu; Chen, Xiaoping; Zhang, Bixiang; Zhu, Peng (Frontiers in Oncology, 2022)
Background and Aim Ruptured hepatocellular carcinoma (rHCC) is classified as T4 according to the TNM staging system with a very poor (does not achieve expected) prognosis, which has always been controversial. This study aimed at assessing the specific impact of different tumor diameters on the posttreatment prognosis of BCLC stage 0/A rHCC patients. Methods Data from 258 patients with BCLC stage 0/A HCC treated in our center from January 2008 to December 2017 were collected, including 143 rHCC patients and 115 patients with non-ruptured HCC (nrHCC). With the help of X-tile software, we determined the cutoff value of the tumor diameter in patients with rHCC. Using 8 cm as the cutoff, we divided rHCC patients into Small-rHCC (n = 96) and Large-rHCC (n = 47) groups, compared the prognoses of the S-rHCC and L-rHCC groups, as well as the prognoses of the two groups with the nrHCC group using the Kaplan–Meier method, and screened the prognostic factors of rHCC patients using the multivariate Cox risk model. Results The OS of the S-rHCC group was significantly higher than that of the L-rHCC group [HR = 2.41 (1.60–3.63)], and the OS of the nrHCC group was comparable to that of the S-rHCC group (P = 0.204). In patients treated with surgery only, OS and RFS were also comparable in the S-rHCC nrHCC group. Meanwhile, multivariate Cox regression analysis revealed that alpha-fetoprotein (AFP), alkaline phosphatase (ALP), and the main method of treatment were also prognostic factors for OS in patients with rHCC. Conclusions Ruptured HCC with a relatively small diameter (≤8 cm) can also achieve the same prognosis as nrHCC patients after aggressive treatment. It is also not recommended to include all patients with rHCC in stage T4.